Genetic variability and character association among the yield and yield attributing components in lentil (Lens culinaris Medik.) - Kumar, Vinod (Bangladesh Journal of Botany, 2020)
Twenty one advanced lines of lentil including three checks were selected. The observations were recorded on five randomly selected plants of each genotype under each replication and per plant. Data were obtained by averaging the values. (i) Pre-harvest observations - days to flowering, days to maturity, (ii) postharvest observations - plant height (cm), pods per plant, no. of branches per plant, yield per plot (kg/ha), 100- seed weight and plant stand (%) considered .The study revealed that characters viz., 100-seed weight (177.5), plant height (66.1) and seed yield (20.7) showed high GCV apprises. In the present investigation out of eight, only seven components (PCs) exhibited more than 5 Eigen value, and showed about 91.289% total variability among the studied traits. Among the others characters days to maturity was positively and significantly correlated by days to 50% flowering and number of pods per plant suggesting early maturity or late maturity depends on flowering which are directly correlated with seed yield and selection of more number of pods plant gives maximum yield.